Obesity-induced cardiac lipid accumulation in adult mice is modulated by G protein-coupled receptor kinase 2 levels. Issue 1 (December 2016) - Lucas, Elisa; Vila-Bedmar, Rocio; Arcones, Alba; Cruces-Sande, Marta; Cachofeiro, Victoria; Mayor, Federico; Murga, Cristina
Abstract Background The leading cause of death among the obese population is heart failure and stroke prompted by structural and functional changes in the heart. The molecular mechanisms that underlie obesity-related cardiac remodeling are complex, and include hemodynamic and metabolic alterations that ultimately affect the functionality of the myocardium. G protein-coupled receptor kinase 2 (GRK2) is an ubiquitous kinase able to desensitize the active form of several G protein-coupled receptors (GPCR) and is known to play an important role in cardiac GPCR modulation. GRK2 has also been recently identified as a negative modulator of insulin signaling and systemic insulin resistance. Methods We investigated the effects elicited by GRK2 downregulation in obesity-related cardiac remodeling. For this aim, we used 9 month-old wild type (WT) and GRK2+/− mice, which display circa 50% lower levels of this kinase, fed with either a standard or a high fat diet (HFD) for 30 weeks. In these mice we studied different parameters related to cardiac growth and lipid accumulation. Results We find that GRK2+/− mice are protected from obesity-promoted cardiac and cardiomyocyte hypertrophy and fibrosis. Moreover, the marked intracellular lipid accumulation caused by a HFD in the heart is not observed in these mice. Interestingly, HFD significantly increases cardiac GRK2 levels in WT but not in GRK2+/− mice, suggesting that the beneficial phenotype observed in hemizygous animals correlates with the maintenance of GRK2 levels below a pathological threshold. Low GRK2 protein levels are able to keep the PKA/CREB pathway active and to prevent HFD-induced downregulation of key fatty acid metabolism modulators such as Peroxisome proliferator-activated receptor gamma co-activators (PGC1), thus preserving the expression of cardioprotective proteins such as mitochondrial fusion markers mitofusin MFN1 and OPA1. Conclusions Our data further define the cellular processes and molecular mechanisms by which GRK2 down-regulation is cardioprotective during diet-induced obesity, reinforcing the protective effect of maintaining low levels of GRK2 under nutritional stress, and showing a role for this kinase in obesity-induced cardiac remodeling and steatosis.